FOREST REGENERATION PROCESS RISK ANALAYSIS AND THE PROPOSED SOLUTION IN VIDUSDAUGAVA FORESTRY - Geršebeka, Simona; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
In this research was explored forest regeneration process and dealt with reforestation related risks. During the research period, where were an evaluation of occurring risk factors and determined the most common form, technology was designed to prevent the risk – remove the effects of artiodactyls. The research was conducted during the period from September 2014 till January 2015, surveying forests in Vidusdaugava forestry and analyzing data from forestry about forest regeneration statistics.